Grammatical interference in Islamic school students’ English narrative writings - Ayu, Dian Pawitri; Nurweni, Ari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Employing a qualitative approach, this study aims to discover the types of grammatical interference that mostly occur in narrative texts written by Indonesian students at a senior high school level. The grammatical interference covered in this article is categorized into two, namely syntactical interference and morphological interference. Moreover, 20 eleventh-grader students of an Islamic school were chosen randomly to be the sample of this research. The students were asked to compose a narrative text with a topic that has been determined by the teacher. Their writings were then analyzed descriptively to find out the dominant types of grammatical interference made by the students. It was revealed that the students encountered morphological inferences related to tenses, articles, subject-plural forms, and pronouns. Besides, syntactical inferences regarding word order, noun phrase, and passive voice are found in the students’ writings. Thus, it implies that students often used the grammatical rules of their first language in composing their writings in English.